2002
DOI: 10.1046/j.1365-2486.2002.00521.x
|View full text |Cite
|
Sign up to set email alerts
|

Annual variation in soil respiration and its components in a coppice oak forest in Central Italy

Abstract: In order to investigate the annual variation of soil respiration and its components in relation to seasonal changes in soil temperature and soil moisture in a Mediterranean mixed oak forest ecosystem, we set up a series of experimental treatments in May 1999 where litter (no litter), roots (no roots, by trenching) or both were excluded from plots of 4 m2. Subsequently, we measured soil respiration, soil temperature and soil moisture in each plot over a year after the forest was coppiced. The treatments did not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

65
406
9
11

Year Published

2005
2005
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 537 publications
(491 citation statements)
references
References 60 publications
65
406
9
11
Order By: Relevance
“…In contrast to other studies (Epron et al, 2001;Hö gberg et al, 2001;Rey et al, 2002), we did not observe marked temporal variation in root respiration fluxes with the exception of the increase in September 2003 (Fig. 4).…”
Section: Root Respiration Sourcescontrasting
confidence: 99%
See 2 more Smart Citations
“…In contrast to other studies (Epron et al, 2001;Hö gberg et al, 2001;Rey et al, 2002), we did not observe marked temporal variation in root respiration fluxes with the exception of the increase in September 2003 (Fig. 4).…”
Section: Root Respiration Sourcescontrasting
confidence: 99%
“…(Edwards & Harris, 1977). Rey et al (2002) reported an annual contribution from root respiration of 23% although previous disturbance at the site were thought to be the cause of this low estimate. It is important to note that in our study, times of highest relative contributions (FRR) were not necessarily times of high root respiration fluxes and thus both quantities should be reported.…”
Section: Root Respiration Sourcesmentioning
confidence: 97%
See 1 more Smart Citation
“…This suggests that extreme drought will alter not only the microbial biomass, but also the community composition for the alternation of microbial C: N. The enhanced ratio of MBC and MBN as showed dominated the fungal with growth deriving more nitrogen nutrient. Various studies have suggested that soil respiration is related to the soil moisture content and soil temperature, and soil respiration will show different sensitivities to soil temperature (Kirschbaum 1995;Rey et al 2002). In our study, the decreased water content weakened the soil respiration significantly.…”
Section: Discussionsupporting
confidence: 40%
“…Root respiration is strongly influenced by aboveground assimilation and growth (Horwath et al, 1994;Robinson and Scrimgeour, 1995). The heterotrophic component of soil respiration is strongly influenced by substrate availability (Raich and Tufekcioglu, 2000;Vasconcelos et al, 2004), which is closely related to aboveground litterfall on a global scale (Raich and Nadelhoffer, 1989;Davidson et al, 2002), and is thus also ultimately driven by aboveground growth and production (Rey et al, 2002). Recently, a microcosm study showed that increased litter inputs under elevated CO 2 would greatly increase microbial respiration in the soil (Liu et al, 2008) and FACE experiments have shown large increases in root respiration, which may be related to increased root biomass or higher specific root respiration rates (Andrews et al, 1999;King et al, 2001;Pregitzer et al, 2008).…”
Section: Introductionmentioning
confidence: 99%